Development of Basic Chemistry Teaching Material Chemical Education Based on Entrepreneurship - Epinur Epinur; Yusnidar Yusnidar; Minarni Minarni (Postgraduate, University of Mataram, 2022)
The current government policy is that scholars do not look for work anymore, but create jobs. Furthermore, the Minister of Education and Culture launched an independent campus policy that carried four policies. The second policy is the right of students to study outside the study program, for example to become entrepreneurs. From the government's policy and the Minister of Education and Culture, entrepreneurship-based basic chemistry teaching materials are needed. The purpose of this research is to develop entrepreneurship-based basic chemistry teaching materials that are feasible theoretically and practically. This teaching material is expected to provide opportunities for students to become entrepreneurs. The development model used is the 4-D model (Four D) developed by Thiagarajan consisting of 4 main stages, namely: Define, Design, Develop and Disseminate. Based on the analysis of student needs, the orientation of the dominant college student is to become an ASN. They are interested in entrepreneurship in the chemical field as a side job. However, they hope that the lecturers in teaching link the course material with the field of business. The teaching materials